Examining the Effects of Caffeine on Isokinetic Strength, Power, and Endurance - Jozo Grgic; Sandro Venier; Pavle Mikulic (Journal of Functional Morphology and Kinesiology, 2022)
This study examined caffeine’s effects on isokinetic strength, power, and endurance. The sample included 25 young, resistance-trained males. The participants were tested on three occasions, in a control trial (no substance ingestion) and following the ingestion of 6 mg·kg−1 of caffeine or placebo. Exercise tests involved isokinetic knee extension and flexion using angular velocities of 60° s−1 and 180° s−1. Analyzed outcomes included peak torque, average power, and total work. For knee extension at an angular velocity of 60° s−1, there were significant differences for: (1) peak torque when comparing caffeine vs. control (Hedges’ g = 0.22) and caffeine vs. placebo (g = 0.30) and (2) average power when comparing caffeine vs. control (g = 0.21) and caffeine vs. placebo (g = 0.29). For knee extension at an angular velocity of 180° s−1, there were significant differences for: (1) peak torque when comparing caffeine vs. placebo (g = 0.26), (2) average power when comparing caffeine vs. control (g = 0.36) and caffeine vs. placebo (g = 0.43), and (3) total work when comparing caffeine vs. control (g = 0.33) and caffeine vs. placebo (g = 0.36). Caffeine was not ergogenic for knee flexors in any of the analyzed outcomes. Additionally, there was no significant difference between control and placebo. In summary, caffeine enhances the mechanical output of the knee extensors at lower and higher angular velocities, and these effects are present when compared to placebo ingestion or no substance ingestion (control).